Estimation of the energy consumption of battery driven electric buses by integrating digital elevation and longitudinal dynamic models: Malaysia as a case study - Saadon Al-Ogaili A.; Ramasamy A.; Juhana Tengku Hashim T.; Al-Masri A.N.; Hoon Y.; Neamah Jebur M.; Verayiah R.; Marsadek M. (Elsevier Ltd, 2023)
Charging (batteries); Dynamic models; Electric automobiles; Energy management; Energy utilization; Forecasting; Information systems; Information use; Large scale systems; Secondary batteries; Digital elevation model; Distributed networks; Generic frameworks; Longitudinal dynamics; Operating environment; Passenger information systems; State-of-the-art methods; Transportation network; Buses; digital elevation model; estimation method; GIS; mapping method; simulator; urban area; Kuala Lumpur [West Malaysia]; Malaysia; West Malaysia